ANALISIS POTENSI KEBANGKRUTAN PERUSAHAAN DENGAN METODE Z-SCORE ALTMAN (STUDI KASUS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2015) - MEINY G. PORAJOUW; TINNEKE TUMBEL; LUCKY F. TAMENGKEL (Universitas Sam Ratulangi, 2016)
ABSTRACT : Maintaining the company's survival in the midst of economic uncertainty and global competition is essential. Companies should conduct an analysis of its financial performance in order to still be able to monitor the state of the company to avoid losses even bankruptcy that threatens the survival of the company. This research aims to analyze the potential bankruptcy of the company by using Altman’s Z-Score method that specifically demonstrate the potential bankruptcy of the company where there are three circumstances, those are safe zone, grey zone, and distress zone. The samples are manufacturing companies listed in Indonesia Stock Exchange during 2013-2015 with sampling purposive technique. The result showed there are two companies in safe zone, one company in grey zone, 18 companies in distress zone, and 10 companies in different zone from year to year. It can be concluded, about 58% of a total sample are in distress zone, so the companies have to immediately find solution in order to prevent the bankruptcy, like do merger. Key words: Altman Z-Score, bankruptcy, manufacturing